2008
DOI: 10.1002/cbdv.200890043
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Antioxidant Formula Based on a Selenium‐Supplemented Carotenoid‐Producing Yeast Biomass

Abstract: Carotenoid-producing yeast species such as Rhodotorula glutinis and Sporobolomyces roseus efficiently accumulated selenium from the growth medium. It was observed that incorporation of selenium into yeast cells during the growth inhibited production of beta-carotenoid and other carotenoid precursors (torularhodin and torulene). The yeasts with high content of the carotenoid pigments and selenium may be used for the preparation of a new type of antioxidant formula that could be directly applied for various huma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 32 publications
(20 reference statements)
0
21
0
Order By: Relevance
“…The results obtained indicate that the most dramatic change was observed in the significantly lowered levels of -carotene, while torularhodin and torulene contents decreased to a lesser extent (Breierova et al, 2008). Previously, it has been shown that Cd, Ni, and Zn induce the opposite effect and stimulate production of -carotene.…”
Section: Production Of Red Yeast Biomass With Accumulated Metalsmentioning
confidence: 76%
See 4 more Smart Citations
“…The results obtained indicate that the most dramatic change was observed in the significantly lowered levels of -carotene, while torularhodin and torulene contents decreased to a lesser extent (Breierova et al, 2008). Previously, it has been shown that Cd, Ni, and Zn induce the opposite effect and stimulate production of -carotene.…”
Section: Production Of Red Yeast Biomass With Accumulated Metalsmentioning
confidence: 76%
“…The other explanation is based on observations that presence of heavy metals results in formation of various active oxygen radicals what, in a turn, induces generation of protective carotenoid metabolites that reduce negative behaviour of free radicals. Such strategy has been applied in several pigment-forming microorganisms to increase the yield of microbial pigments (Breierova et al, 2008;Rapta et al, 2005). In order to achieve rapid carotenoid overproduction, various stimulants can be added to the culture broth.…”
Section: Specific Supplements and Exogenous Factors Enhancing Metabolmentioning
confidence: 99%
See 3 more Smart Citations